(untitled) (Reflection and Critique Law Magazine, 2020)
This article aims to study the discussion about the restriction on blood donation to men who have had sex with men (MSM) for a period of 12 (twelve) months after sexual intercourse, as set forth in Ordinance 158 of 04 of February 2016, of the Ministry of Health of the Federative Republic of Brazil, in its article 64, and in ANVISA’s RDC 34 of June 11, 2014, in its article 25. This analysis is made in the light of the constitutional principles of human dignity equality, freedom and non-discrimination, finally, the theme will be analyzed towards Robert Alexy’s weighting method. Keywords: Weighting; Constitutional principles; Blood donation; Homosexual relationships.